The Impact of Online Lecture in The Covid-19 Pandemic Towards The Course Material Understanding (Explorative Study to Islamic Education Postgraduate Students at IAIN Salatiga) - Rahmawati, Aida Dwi; Khamid, Abdul (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
The purpose of this study was to know about student’s material understanding because implementation online lectures in pandemic. Then, the positive impact of conducting online lectures and inhibiting factors. This research is qualitative approach. Primary data by Google Form and secondary data by articles. By this, the PAI Postgraduate online implementation strategy utilizing whatsapp group, zoom, and google form. The positive impacts, distant learning prevent outbreaks; flexible lecture time; easier to understand; add insight related to the use of technology; saving cost. While the inhibiting effects is hard to get a comprehensive explanation; difficult signals; lectures who have assignments without explanation; hard to find sources.